The EU’s accession to the ECHR and the Dublin Regulation: is accession still desirable? - Gomes Beirão, Joana (UNIO – EU Law Journal, 2022)
This paper addresses whether the European Union’s accession to the European Convention on Human Rights (ECHR) is still possible and desirable considering Opinion 2/13, as well as the caselaw of the Court of Justice of the European Union (CJEU) and the European Court of Human Rights (ECtHR) on the application of the Dublin Regulation. It argues that accession is still possible, though negotiations of an accession agreement compliant with the conditions imposed by Opinion 2/13 may prove particularly difficult in practice. Additionally, it argues that accession is desirable if the principle of mutual trust is not upheld over human rights, since accession in these conditions would enhance human rights protection in the context of the application of the Dublin Regulation.